Residual stress and wear studies of deep cryogenically treated SAE 52100 bearing steel / M. Shunmuga Priyan and R. Sri Siva - Priyan, M. Shunmuga; Siva, R. Sri (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
In this work mainly used to study the diffraction phases and residual stress on SAE 52100 bearing steel in which applying the effect of cryogenic treatment at various operating conditions. The tensile residual stress behavior is assessed by X-Ray diffractometer as per the ASTM standard E2860-12. Refinement of carbide particle by deep cryogenic treatment (DCT) is often proposed in literature as the improvement for the residual stress in the bearing steel. X-Ray diffractometer technique includes the identification of phases and quantitative analysis of crystalline chemical compounds, residual macro and micro stress analyses. The tensile residual stress increased by +30Mpa owing to deep cryogenic treatment when compared with that of conventional heat treatment (CHT). Moreover, the DCT process improves the hardness of SAE 52100 bearing steel by 15% compared to CHT process.